2017
DOI: 10.1007/s11999-016-5071-1
|View full text |Cite
|
Sign up to set email alerts
|

Operative Fluoroscopic Correction Is Reliable and Correlates With Postoperative Radiographic Correction in Periacetabular Osteotomy

Abstract: Background Intraoperative fluoroscopy is commonly used to both guide the osteotomy and judge correction of the acetabular fragment in periacetabular osteotomy (PAO). Prior studies that have compared intraoperative fluoroscopic correction with postoperative radiographic correction were small studies that did not report intra-or interreader reliability. Questions/purposes (1) What is the correlation between intraoperative fluoroscopic correction in PAO compared with the correction seen on postoperative radiograp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 19 publications
3
19
0
Order By: Relevance
“…Fluoroscopy is commonly used to judge fragment correction during PAO to correct acetabular dysplasia. Accuracy of fluoroscopy in judging the correction obtained has been demonstrated for LCEA, TA, and ACEA [12,22]. Our study further validates these three measures as reliable and accurate for judging correction intraoperatively with a mean difference of # 2°for all three measures.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…Fluoroscopy is commonly used to judge fragment correction during PAO to correct acetabular dysplasia. Accuracy of fluoroscopy in judging the correction obtained has been demonstrated for LCEA, TA, and ACEA [12,22]. Our study further validates these three measures as reliable and accurate for judging correction intraoperatively with a mean difference of # 2°for all three measures.…”
Section: Discussionsupporting
confidence: 76%
“…Therefore, it did not address interrater reliability and was underpowered to address intrarater reliability [12]. A larger study by one of the current authors evaluated the use of the LCEA and TA for intraoperative correction and showed similar intra-and interrater reliability as those reported here for the LCEA and TA [22]. However, this study only looked at lateral coverage with LCEA and TA.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations